The role of universities in the development of the local knowledge base: supporting innovation ecosystems through skills development and entrepreneurship. (16th February 2022) - Rosli, Ainurul; Cacciolatti, Luca
Regional competitiveness can be achieved by different setups in the regional innovation system (RIS), contrasting the liberal, industry-driven model of Silicon Valley. Such model commonly adds value to the innovation ecosystem by leveraging the weight of private initiative. However, other actors in the triple helix can also play an important role in contributing to thriving novel innovation systems. We present two case studies, i.e.: 1) the northern powerhouse; 2) midlands engine. These are both European models, which outline the role that universities play in supporting the development of the local knowledge base to build resilient and sustainable innovation systems. Our findings suggest the importance of the upgrading of the regional learning capabilities and overall workforce upskilling. The policy implications suggest policy makers could shape the role of the centres of knowledge through the coordination of regional efforts and by applying KBD solutions to the development of RIS.